THE DEVELOPMENT OF SPHERICAL ROBOTS WITH HYBRID DELIBERATIVE/REACTIVE ARCHITECTURE FOR SWARM PATROL - Saputra & Muhammad Akbarul Aizs, Cahya
Swarm robotics is the study of how to coordinate a large group of robots that are relatively simple through the application of several rules. The applications of this technology are very diverse, such as to patrol. The development of this application is supported by the presence of a spherical robot design, which has many advantages for patrolling. For this reason, it’s necessary to develop a swarm control system for spherical robots to conduct patrols so that they can run optimally.